The Effect of Autonomy-Based Learning Environment and Critical Thinking Skills on Language Performance and Intrinsic Motivation: an Experimental Study on EFL Students - Sayfadin Sharif (Tadbir : Jurnal Studi Manajemen Pendidikan, 2026)
This experimental study investigates the combined effects of autonomy-based learning environments and critical thinking skills training on language performance and intrinsic motivation among EFL students. A 2×2 factorial design was employed with 120 second-year students from the Department of English Language, College of Education, Salahaddin University-Erbil, randomly assigned to four groups: autonomy support only, critical thinking training only, combined intervention, and traditional instruction control group. Data were collected through standardized language proficiency tests and intrinsic motivation scales over a 16-week intervention period during the 2024-2025 academic year. Statistical analyses including two-way ANOVA revealed significant main effects for both autonomy support and critical thinking training, with the combined intervention group demonstrating the highest gains in language performance and intrinsic motivation. Results suggest that integrating learner autonomy support with explicit critical thinking instruction creates synergistic effects that substantially enhance EFL learning outcomes beyond either approach implemented independently.